Self-consistent determination of the fictitious temperature in thermally-assisted-occupation density functional theory. Issue 80 (30th October 2017) - Lin, Chih-Ying; Hui, Kerwin; Chung, Jui-Hui; Chai, Jeng-Da
Abstract : We propose a self-consistent scheme for the determination of the fictitious temperature in thermally-assisted-occupation density functional theory (TAO-DFT) [J.-D. Chai, J. Chem. Phys., 2012, 136, 154104]. Abstract : We propose a self-consistent scheme for the determination of the fictitious temperature in thermally-assisted-occupation density functional theory (TAO-DFT) [J.-D. Chai, J. Chem. Phys., 2012, 136, 154104], a very efficient electronic structure method for studying nanoscale systems with strong static correlation effects (which are "challenging systems" for traditional electronic structure methods). In comparison with semilocal density functionals in Kohn–Sham density functional theory (KS-DFT), the corresponding semilocal density functionals in TAO-DFT (with the self-consistent fictitious temperature) provide significant improvement for systems with strong static correlation effects ( e.g., the dissociation of H2 and N2 and twisted ethylene), and retain very similar performance for systems without strong static correlation effects ( e.g., thermochemistry, kinetics, and reaction energies), yielding a much more balanced performance for both types of systems than those in KS-DFT. Besides, a reliably accurate description of noncovalent interactions can be efficiently achieved via the inclusion of dispersion corrections in TAO-DFT. Relative to the previous system-independent fictitious temperature scheme in TAO-DFT, the present self-consistent fictitious temperature scheme in TAO-DFT is generally superior in performance for a very broad range of applications.